Exploración Del Estado Afectivo En Caninos Maltratados Y No Maltratados A Través De Pruebas Cualitativas Y Cuantitativas De Comportamiento (2024)
The study explored the affective state of 30 dogs in Bogotá, Colombia, comparing 15 abused (M) and 15 non-abused (NM) dogs through behavioral tests and interviews with their handlers. The dogs participated in an ethological test involving visual, auditory, and tactile contact, and the handlers completed the C-BARQ questionnaire to assess behavior and temperament.